2012
DOI: 10.1016/j.yhbeh.2012.04.015
|View full text |Cite
|
Sign up to set email alerts
|

The role of AT1 receptor-mediated reproductive function in renovascular hypertension in male rats

Abstract: There is an association between hypertension and reproductive dysfunction. Angiotensin II (Ang II) is involved in the pathogenesis of hypertension and the regulation of reproduction. The present study aimed to determine whether the angiotensinergic system mediates the effects of hypertension on reproductive function in male rats subjected to a two-kidney, one-clip (2K1C) model. Sexual behavior parameters, gametogenesis and plasma concentrations of Ang II, testosterone, prolactin and corticosterone were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
1
5
0
Order By: Relevance
“…15 Even less attention has been given to sexual dysfunction that may affect subjects with renovascular hypertension. Confirming studies in male rats, 11,12 the data presented here indicate that renovascular hypertension promotes an overall reduction in female reproductive function in rats. Specifically, 2K1C female rats show decreased oocyte numbers, sexual behavior, and LH levels during the proestrus afternoon when compared with control sham rats.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…15 Even less attention has been given to sexual dysfunction that may affect subjects with renovascular hypertension. Confirming studies in male rats, 11,12 the data presented here indicate that renovascular hypertension promotes an overall reduction in female reproductive function in rats. Specifically, 2K1C female rats show decreased oocyte numbers, sexual behavior, and LH levels during the proestrus afternoon when compared with control sham rats.…”
Section: Discussionsupporting
confidence: 83%
“…In the animal literature, only a few studies using the well-established rodent model of renovascular hypertension-the 2-kidney, 1-clip (2K1C) Goldblatt model 9,10 -have analyzed reproductive function in male rats, reporting a drastic impairment in reproductive functions. 11,12 Clinical data support the suggestion that sexual dysfunction is more frequent in women than in men. 13,14 Despite this higher prevalence, clinical and preclinical studies on female sexual dysfunction are remarkably scarce, and the mechanisms by which hypertension interferes with female reproductive function are still not fully understood.…”
Section: Doi:101093/ajh/hps026mentioning
confidence: 65%
See 2 more Smart Citations
“…Ang II can affect the expression of hormonal regulators of stress, such as corticosterone [ 46 ]. However, plasma corticosterone evaluated in rats induced to hypertension by the 2K1C model for 4 weeks showed no significant changes in the 2K1C group [ 47 ]. In another study, Müller et al [ 48 ] showed that there was no change in the basal level of corticosterone after systemic treatment of rats with exogenous angiotensin.…”
Section: Discussionmentioning
confidence: 99%